Understanding biofilm--phage interactions in cystic fibrosis patients using mathematical frameworks - Emerenini Blessing O.; Hartung Doris; Reyes Grimaldo Ricardo N. G.; Canner Claire; Williams Maya; Agyingi Ephraim; Osgood Robert (Computational and Mathematical Biophysics)
When planktonic bacteria adhere together to a surface, they begin to form biofilms, communities of bacteria. Biofilm formation in a host can be extremely problematic if left untreated, especially since antibiotics can be ineffective in treating the bacteria. Certain lung diseases such as cystic fibrosis can cause the formation of biofilms in the lungs and can be fatal. With antibiotic-resistant bacteria, the use of phage therapy has been introduced as an alternative or an additive to the use of antibiotics to combat biofilm growth. Phage therapy utilizes bacteriophages that attack bacteria, to penetrate and eradicate biofilms. To evaluate the effectiveness of phage therapy against biofilm bacteria, we create a phage-biofilm model with ordinary differential equations and a stochastic model. We considered three possible cases for the stability of disease-free equilibrium; by model simulations and parameter alterations in both models, we investigated the effect of bacteria–phage interactions alongside biofilm bacteria cell detachment from the biofilm phase to the planktonic phase, and how these will affect the efficiency of phage therapy against bacteria. Our results show that, by increasing the phage mortality rate, the biofilm growth can be balanced, which makes it more vulnerable to antibiotics. Thus, phage therapy is an effective aid in biofilm treatment.